ANALISIS EFISIENSI USAHATANI JAGUNG DI KECAMATAN MADAPANGGA KABUPATEN BIMA - efendy efendy; addinul yakin; wanda widianti (JURNAL AGRIMANSION, 2023)
The aims of this study were to: (1) examine the effect of the use of production factors on maize production in Madapangga sub-district, Bima district; (2) Analyzing the efficiency of the use of production factors in corn farming in Madapangga Subdistrict, Bima Regency; (3) Knowing the advantages of corn farming in Madapangga Subdistrict, Bima Regency. The method used in this research is descriptive method. This research is located in Madapangga Subdistrict, Woro Village and Tonda Village and determined by purposive sampling on the basis that these two villages have the most corn farmers and the area of ​​corn farming land. The number of respondents was determined as many as 30 respondents and selected by proportional random sampling. Sources of data used are primary data and secondary data. The results of the research are: (1) Production factors (production inputs) that affect the production of corn farming are production factors: seeds (X2), urea (X3) and the use of labor (X7), while other production factors are phoska fertilizer (X4 ), Pelangi fertilizer (X5) and pesticides (X6) had no significant effect on corn farming production. (2) Based on the results of the analysis of the efficiency of input use in corn farming in the District of Madapangga, Bima Regency, it is known that the use of seed input (X2), urea fertilizer (X3), phoska fertilizer (X4) and the use of labor (X7) is not efficient because the value of the efficiency ratio NMP/BKM > 1 then it is necessary to add input, while for inputs Production of rainbow fertilizers (X5) and pesticides (X6) is not efficient because the value of the efficiency ratio of NMP/BKM is < 1 and it is necessary to reduce the amount of use of production inputs. (3) The profit earned on corn farming in Madapangga Subdistrict, Bima Regency in 2022 is Rp. 40,003,234 per arable area or 25,808,538 per hectare.